Translating Science Into Business Innovation: The Case of Open Food and Nutrition Data Hackathons - Tucci, Christopher; Viscusi, Gianluigi; Gautschi, Heidi (Frontiers in Nutrition, 2018)
In this article, we explore the use of hackathons and open data in corporations' open innovation portfolios, addressing a new way for companies to tap into the creativity and innovation of early-stage startup culture, in this case applied to the food and nutrition sector. We study the first Open Food Data Hackdays, held on 10–11 February 2017 in Lausanne and Zurich. The aim of the overall project that the Hackdays event was part of was to use open food and nutrition data as a driver for business innovation. We see hackathons as a new tool in the innovation manager's toolkit, a kind of live crowdsourcing exercise that goes beyond traditional ideation and develops a variety of prototypes and new ideas for business innovation. Companies then have the option of working with entrepreneurs and taking some the ideas forward.